EFEKTIVITAS PELAYANAN PENANGANAN PASIEN DI INSTALASI GAWAT DARURAT (IGD) RUMAH SAKIT UMUM DAERAH PETALA BUMI KOTA PEKANBARU - Rizky, Angga; ", Zulkarnaini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study describes the Effectiveness of Patient Handling Installation services Emergency department (ED) Hospital Petala Bumi Pekanbaru. The phenomenon of the background for this research is the discovery of a complaint of some patients and families of patients quality of services contained in the General Hospital Petala Bumi city of Pekanbaru in terms of hospitality officer, when handling emergency patients long enough until the service process convoluted where the service activities in the emergency room installation requires administrative process as soon as possible.This study uses the theory Sterrs consisting of four indicators include the ability to adjust, work productivity, job satisfaction, resource utilization (human resources capability). The research method used descriptive analysis with collection through observation, interview, and literature study.The results of the study authors found the effectiveness of the services contained in the general hospital petala bumi Pekanbaru city has not gone up. It is seen from the ability of self menyesuaian officer of duty evidenced by the presence of a transfer of inpatient room to the emergency room so that these officers do not yet understand the task that is in the emergency room. Aside from the ability to adjust, employee productivity has not gone to what was expected authors found the presence of patients waiting to be handled by a doctor. Due to the lack of the number of officers who will be treating patients in the emergency room. Factors affecting the effectiveness of the treatment of patients progressed less in the plant emergency low level of adjustment of service personnel as well as the lack of workforce services.Keywords: Effectiveness, Handling Services